PENGEMBANGAN MODEL PENGUKURAN CELAH ANTARPANEL PINTU MOBIL MENGGUNAKAN JARINGAN SARAF TIRUAN DAN PENDETEKSIAN KONTUR - Rizkyputra, Shergio
PT X is an automotive manufacturing company with 5 production plants located in Indonesia, whose vehicles are sold domestically and exported internationally. There exists a final inspection station where each vehicle unit are examined for body-fitting defects within their production line. Currently, the final inspection is performed visually by 4 human operators. The addition of human operators is also expected to reduce the body-fitting inspection time from 96 seconds to 86 seconds.